STRATEGI KOMUNIKASI PEMASARAN TERPADU (IMC) KEBUN RAYA EKA KARYA BALI DALAM MENINGKATKAN BRAND AWARENESS - Kartini, Ni Made; Joni, I Dewa Ayu Sugiarica; Pradipta, Ade Devia (E-Jurnal Medium, 2024)
The largest botanical garden in Indonesia and one of Bali's protected forests is Eka Karya Bali Botanical Garden. Located in the Bali Province's Candikuning Village, Baturiti District, and Tabanan District. Established in 1959, it has an area of 157.5 hectares and has a tagline “Let's go to the Botanical Garden”. Have brand awareness as a